2017
DOI: 10.1186/s12941-017-0233-x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular determination of antimicrobial resistance in Escherichia coli isolated from raw meat in Addis Ababa and Bishoftu, Ethiopia

Abstract: BackgroundConsumption of meat contaminated by E. coli causes a serious illness and even death to affected individuals. Recently the emerging of antibiotic resistant foodborne E. coli poses serious public health risks worldwide. However, little is known about the antibiotic resistance profile of E. coli in Ethiopia. This study aimed to determine the prevalence and Antimicrobial resistance (AMR) status of E. coli isolated from different type of meat.MethodsOverall 292 samples were collected from December 2015 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
22
8
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 31 publications
15
22
8
1
Order By: Relevance
“…Besides, low doses of tetracycline have been used to control weaning diarrhoea and also included in the feed as antibiotic feed additives (AFAs) for growth promotion [5]. The results observed in this study are in agreement with studies done in Ethiopia, Iran, and Pakistan [4144]. Meanwhile, our findings contradict findings of earlier studies done in South Africa and Poland that reported lower prevalences [25,29].…”
Section: Discussionsupporting
confidence: 87%
“…Besides, low doses of tetracycline have been used to control weaning diarrhoea and also included in the feed as antibiotic feed additives (AFAs) for growth promotion [5]. The results observed in this study are in agreement with studies done in Ethiopia, Iran, and Pakistan [4144]. Meanwhile, our findings contradict findings of earlier studies done in South Africa and Poland that reported lower prevalences [25,29].…”
Section: Discussionsupporting
confidence: 87%
“…According to the World Organization for Animal Health (OIE, 2018), penicillin G, tetracycline, and amoxicillin-clavulanic acid are "critically important antimicrobial agents," while cefazolin and cefalotin are categorized as "highly important antimicrobial agents" in veterinary medicine (OIE, 2018). High levels of resistance to such antimicrobials have also been reported by other authors in bacteria isolated from beef (Cameron & McAllister, 2016;EFSA & ECDC, 2019;Hiroi et al, 2012;Jaja, Bhembe, Green, Oguttu, & Muchenje, 2019;Messele et al, 2017). The high prevalence of resistance or reduced susceptibility to antibiotics noted in the present work is, nonetheless, surprising…”
Section: Antibiotic Resistance In E Coli Isolates From Beef Preparsupporting
confidence: 86%
“…Boost incidence of resistance toward chloramphenicol is mostly owing to an excessive application of this forbidden antibioticin poultry fields. Boost incidence of resistance toward chloramphenicol was also conveyed in investigations conducted on the United States [27], Ethiopia [28] and Iran [29]. Similar phenotypic profiles of antibiotic resistance were also conveyed from South Africa [30] (boost incidence of ampicillin and tetracycline), India [31] (boost incidence of resistance toward gentamicin, cephalothin, erythromycin, kanamycin andamikacin), Mexico [32] (boost incidence of resistance toward ampicillin, chloramphenicol, trimethoprimsulfamethoxazole and cephalothin) and South Korea [33] (boost incidence of resistance toward streptomycin, ampicillin, amikacin and tetracycline).…”
Section: Discussionmentioning
confidence: 99%